Attachment to God and death anxiety in later life : does race matter? - Jung, Jong Hyun (2019)
Research suggests that religion plays a critical role in individuals’ attitudes toward death in later life. The purpose of this study is to investigate whether a previously unexamined aspect of religion—secure attachment to God—is associated with death anxiety among U.S. older adults and whether this association varies across race. Using longitudinal data from a representative sample of adults aged 65 and older (N=936), the analyses reveal that secure attachment to God is associated with a decrease in death anxiety over time. Further, the negative association between secure attachment to God and change in death anxiety is greater for older Blacks than their White counterparts. These results indicate that religion serves a protective function against death anxiety in later life. Moreover, religion provides greater psychological benefits for older Blacks than older Whites, reinforcing a long-standing claim that religion is particularly valuable for individuals from marginalized backgrounds.